Staged progress tests for athletic training process design in sport schools - Khristov, V. V.; Makaridin, D. N.; Alekseeva, M. V.; Soloshenko, N. B. (Theory and Practice of Physical Culture, 2017)
The study considers priorities of the athletic training process design and management initiatives in the long-term training system design to improve the education and training process; and describes a newly proposed training efficiency improvement model applied at Tyumen sport schools. The new training models include: athletes` physical health and fitness monitoring system; analyses of the health progress test data; and actions to update the education and training systems. New advanced training course for sport school managers, practitioners, senior coachers and instructors in every sport discipline may be described as one more step in the efforts to improve the long-term athletic training system design and management component. The study reports benefits of the new training process design and management model as verified by the athletes` physical and functional progress tests supported by staged medical examinations at the advanced sport specialisation and sport excellence stages, with cyclic sport disciplines at Tyumen sport schools taken for the case study.